Perlindungan Hukum Dalam Penataan Pedagang Kaki Lima Dalam Rangka Peningkatan Taraf Hidup Pedagang(Studi Kasus Di Kawasan Manahan Solo) - Vitasari, Nur, Wardah Yuspin, S. H., Mkn,PhD (2017)
This research aims to know the governing regulation on small bussiness protection, to examine the relocation process of a better place for doing bussiness in order to avoid social conflict, and to know what efforts undertaken by the Government of Surakarta that relocation do can improve the living standards of street vendors. The method I use is empirical juridical approach. This type of research used by the author in this study is the use descriptive research. The location of research in the Department of Market Management Surakarta, UPTD Facility Sports, Ministry of Youth and sports Surakarta, as well as the Association of Street Vendors at Manahan Stadium Solo. Using primary data sources and secondary data. Methods of data collection in this study using techniques literature study and field study by interview with sources that are considered knows seated problems. Based on the results of research and discussion it can be concluded that the Government of Surakarta in an effort to improve and empower street vendors a way to relocate and provide new places that are considered more strategic, and seeks to empower street vendors to improve the quality of human resources, to provide capital assistance trader pavement, as well as mentoring and business development.